Making nonprofits work : a report on the tides of nonprofit management reform - Light, Paul Charles (Aspen Institute : Brookings Institution Press, 2000)
"In Making Nonprofits Work, Paul C. Light charts the current trends of management reform in the nonprofit sector and assess the climate for reform at the local and national levels. Light examines the four popular philosophies, or "tides," being advocated - scientific management, liberation management, war on waste, and watchful eye - offering examples and caveats from a portfolio of recent experience."